Thailand's energy-related carbon dioxide emissions from production-based and consumption-based perspectives. (October 2019) - Ninpanit, Panittra; Malik, Arunima; Wakiyama, Takako; Geschke, Arne; Lenzen, Manfred
Abstract: Over the past few decades, Thailand has been one of the highly open economies and one of the most successful countries in applying the export-led growth model. At the same time, carbon dioxide (CO2 ) emissions released in Thailand tripled between 1990 and 2015. To examine how international trade plays a role in shaping Thailand's CO2 emissions inventory, we compare emissions under both production-based and consumption-based accounting over 1990–2015 and disaggregate total CO2 emissions into traded and non-traded parts. We also use a multi-regional input-output database for performing a structural decomposition analysis (SDA) to investigate the factors contributing to changes in CO2 emissions. We find that Thailand continually stood out as a net carbon exporting country. CO2 embodied in exports accounted, on average, for 40% of domestically produced emissions. Our SDA results suggest that traded and non-traded emissions grew mainly due to increasing per-capita consumption in Thailand and abroad. The retarding effect from energy efficiency improvement was significant but not sufficient to reduce emissions. Highlights: Thailand's production-based CO2 surpassed consumption-based CO2 by 23% per year. 40% of production-based CO2 in Thailand was a result of export production. Improvements in energy efficiency helped to cancel around half of the impact from an increase in per-capita consumption. To achieve its greenhouse gas emissions target, Thailand should accelerate the renewable energy transition.